Electronics Payment Decisions of the Indonesian Urban Households: A Nested Logit Analysis of the Effects of the Payment Characteristics - Sahabat, Imaduddin; Dartanto, Teguh; Passay, Haidy A.; Widyawati, Diah (International Journal of Economics and Financial Issues, 2017)
Despite the dominance of cash method, electronic transactions have emerged in urban Indonesia. Existing studies focused on the macro impact of such transaction in developed countries. Limited attention has been paid to study consumers’ preference of payment method at micro level due to attributes of payment method associated with consumer preferences. This study attempts to analyze household’s decision associated with preference of electronic payments using data of 936 urban households in six municipalities in Jakarta and East Java, focusing on the effect of payment system characteristics on the preferred payment method. Nested logit model is employed as the household’s decision can be assumed to follow asequential process. The results indicate that payment method’s attributes such as security, cost, reward and acceptance, have significant impact on electronic payment preference. It should be noted that debit card and credit transfer users are the most sentitive to a change in unit of security, cost and acceptance, and credit card users are more likely affected by the changes in reward. Other empirical findings include that the ease of access to the banking infrastructure and number of minimarkets increases the preference of electronic payments. In addition, the choice is highly dependent on age, education, occupation status and income. Moreover, the empirical analysis explicitly modeled the pattern of correlations among alternatives by a nested logit model and the inclusive value of 0.661 also proofed that the decision making process is occurred in sequence. This implies that one paymet method is more likely to compete with another payment method of thesame electonic payments than the payment methods of cash payment alternative. In conclusion, this study confirms attributes that are influential to further induce household’s use of electronic payment methods. Keywords: Payment System, Household Behavior, Electronic Payment JEL Classifications: D1, E42